Combined scanning tunneling microscopy (STM) & surface stress measurements (SSM) of chemical reactions on semiconductor surfaces : oxidation of the Si(111)-(7x7)surface - Meehan, David E. (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
A novel combined scanning tunneling microscopy (STM) and surface stress measurement (SSM) system has been developed to allow absorbate-induced changes in surface stress to be measured and related to the structural and electronic changes causing them in situ and with atomic resolution. Here, the system is used to investigate the oxidation of the Si(111)-(7 x 7) surface at room temperature. The site-specific evolution of surface stress is measured and associated with relief of the intrinsic tensile stress of the (7 x 7) unit cell. It is shown that stress relief is greatest in the faulted half of the unit cell, consistent with the known larger tensile stress of that half. It is further shown that metastable species proposed to exist on the surface at room temperature do not have significant stress signatures. A widely accepted reaction model is also extended to account for the known preference of oxygen for reacting with the faulted half of the unit cell. Finally, the validity of three reaction mechanisms proposed in the literature is assessed in terms of the above findings. The implications for the room-temperature reaction mechanism are discussed.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.